1999
DOI: 10.1590/s0102-05361999000200016
|View full text |Cite
|
Sign up to set email alerts
|

Competição de cultivares de alface sob cultivo hidropônico 'NFT' em três diferentes espaçamentos

Abstract: Com o objetivo de avaliar o desempenho de seis cultivares de alface do tipo lisa (Babá de Verão, Brasil 303, Elisa, Karla, Lívia e Monalisa) em três espaçamentos (25 x 20, 25 x 25 e 25 x 30 cm), cultivadas em sistema hidropônico 'NFT', realizou-se um experimento na Fazenda Experimental da Universidade de Marília (SP), no período de 23 de setembro a 21 de novembro de 1997. Foram avaliadas as características comprimento de caule, produção de matéria fresca por planta e por área e produção de matéria seca da part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
1
5
0
3
Order By: Relevance
“…Regarding the spacing effect, Gualberto et al (1999) evaluated the competition of lettuce cultivars in three spacings (25 × 20; 25 × 25; and 25 × 30 cm) and did not find significant differences for the isolated effect of spacing, as observed in the present study (Table 1).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Regarding the spacing effect, Gualberto et al (1999) evaluated the competition of lettuce cultivars in three spacings (25 × 20; 25 × 25; and 25 × 30 cm) and did not find significant differences for the isolated effect of spacing, as observed in the present study (Table 1).…”
Section: Resultssupporting
confidence: 55%
“…Lavínia (Table 2). Likewise, Gualberto et al (1999), when evaluating the competition of lettuce cultivars under three spacings (25 × 20; 25 × 25; and 25 × 30 cm), found no significant differences for the isolated effect of spacing on shoot dry weight. However, Echer et al (2001) found that as spacing decreases and population density increases, within certain limits, there is a trend toward increased total production per area, possibly resulting in higher profitability for the producer.…”
Section: Resultsmentioning
confidence: 94%
“…Gualberto et al (1999) obtiveram, na primavera, boa produtividade com a cultivar Babá de Verão, porém sua qualidade foi afetada pelo pendoamento precoce. Na Tabela 2, os maiores valores de comprimento do caule (CCA) obtidos com a cultivar Babá de Verão, em relação à Regina, confirmam a maior tendência ao pendoamento precoce da primeira cultivar.…”
Section: Resultsunclassified
“…Os recipientes foram arranjados de modo que se obtivesse espaçamento de 0,22 m entre plantas. As soluções nutritivas (solução 1 e 2) foram calculadas com base no proposto por diversos autores (Bloom-Zandstra & Lampe, 1983;Ikeda & Osawa, 1984;Os & Kuiken, 1984;Prince & Koontz, 1984;Steiner, 1984;Suzuki et al, 1984;Cramer & Spurr, 1986).…”
Section: Methodsunclassified
“…The nutrient solutions were composed of a conventional hydroponic solution (HS) and two wastewater solutions from tilapia (Oreochromis niloticus) with diets of 15% (WS15%) and 18% (WS18%) of crude protein, with 50% of the feed provided at 9 am and the other half at 4 pm. The HS was composed of a mix of essential macro and micronutrients from organic fertilizer for hydroponics (NPK+8 nutrients, Forth Hortaliças™), applying, per liter, 236.3 mg of N, 39.0 mg of P, 224.9 mg of K, 228.0 mg of Ca, 33.7 mg of Mg, 46.3 mg of S, 0.24 mg B, 0.02 mg Cu, 5.0 mg Fe, 0.23 mg Mn, 0.03 mg Mo, and 0.05 mg Zn, according to Gualberto et al (1999).…”
Section: Methodsmentioning
confidence: 99%